2022
DOI: 10.1186/s12870-022-03663-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of grape ABA receptor gene VaPYL4 enhances tolerance to multiple abiotic stresses in Arabidopsis

Abstract: Background Abscisic acid (ABA) plays a crucial role in abiotic stress responses. The pyrabactin resistance (PYR)/PYR-like (PYL)/regulatory component of ABA receptor (RCAR) proteins that have been characterized as ABA receptors function as the core components in ABA signaling pathway. However, the functions of grape PYL genes in response to different abiotic stresses, particularly cold stress, remain less studied. Results In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Heatmap of transcript levels for genes and contents for metabolites that are involved in the biosynthesis of phenylpropanoids. signaling pathway, and previous studies reported that PYL genes are positive regulators related to stress response in ABA signaling transduction, such as PYL4 and PYL9 (Nai et al, 2022;Ren et al, 2022). In our study, we found that three PYR/PYL genes (c25218.graph_c0, c34730.graph_c0, and c49758.graph_c0) were significantly induced by cold treatment (Figure S18a), which suggested that the ABA signaling pathway plays an important role in the response of V. sativa to cold stress.…”
Section: Plant Hormones Involved In the Response Of V Sativa To Cold ...supporting
confidence: 75%
See 1 more Smart Citation
“…Heatmap of transcript levels for genes and contents for metabolites that are involved in the biosynthesis of phenylpropanoids. signaling pathway, and previous studies reported that PYL genes are positive regulators related to stress response in ABA signaling transduction, such as PYL4 and PYL9 (Nai et al, 2022;Ren et al, 2022). In our study, we found that three PYR/PYL genes (c25218.graph_c0, c34730.graph_c0, and c49758.graph_c0) were significantly induced by cold treatment (Figure S18a), which suggested that the ABA signaling pathway plays an important role in the response of V. sativa to cold stress.…”
Section: Plant Hormones Involved In the Response Of V Sativa To Cold ...supporting
confidence: 75%
“…A total of 16 DEGs related to ABA signal transduction were obtained in the present study, and the expression level of most genes was induced during cold treatment except for three genes (Figure S17a). The pyrabactin resistance (PYR)/PYR‐like (PYL)/regulatory component of ABA receptor (RCAR) proteins that have been characterized as ABA receptors function as the core components in the ABA signaling pathway, and previous studies reported that PYL genes are positive regulators related to stress response in ABA signaling transduction, such as PYL4 and PYL9 (Nai et al, 2022; Ren et al, 2022). In our study, we found that three PYR / PYL genes (c25218.graph_c0, c34730.graph_c0, and c49758.graph_c0) were significantly induced by cold treatment (Figure S18a), which suggested that the ABA signaling pathway plays an important role in the response of V. sativa to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of ABA receptor genes leads to enhanced salt tolerance. For example, overexpression of rice OsPYL5 and grape VaPYL4 enhances salt tolerance in Arabidopsis, respectively [ 31 , 32 ]. Various transcription factors, such as ABF, act downstream of SnRK2 to regulate the synthesis of compatible osmolytes in response to salt stress [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PYLs are the core regulators of ABA signal transduction in plants. Multiple reports have shown that PYLs can improve plant sensitivity to drought, osmotic stress, and cold heat stress [ 73 , 74 , 75 , 76 , 77 , 78 ]. In our study, the expression of two (CsaV3_3G033450, CsaV3_5G000620, CsaV3_5G010560, and CsaV3_6G001990) and one (CsaV3_4G026530) PYL genes was upregulated in the LC24 vs. L24 and in both the LC3 vs. L3 and LC24 vs. L24 pairwise comparisons, respectively ( Tables S2–S5 ).…”
Section: Discussionmentioning
confidence: 99%